2011
DOI: 10.1007/s00586-010-1673-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a clinical prediction rule to identify patients with neck pain who are likely to benefit from home-based mechanical cervical traction

Abstract: The objective of the study was to identify the population of patients with neck pain who improved with home-based mechanical cervical traction (HMCT). A prospective cohort study was conducted in a physical therapy clinic at a local hospital. Patients with neck pain referred to the clinic for physical therapy were included in the study. A HMCT program was given to participants for 2 weeks. The patient's demographic data, Numerical Pain Scale (NPS) score, Neck Disability Index (NDI) and FearAvoidance Beliefs Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
0
16
2
2
Order By: Relevance
“…Mechanical cervical traction is an intervention that is often recommended for the treatment of patients with neck pain 8 . However, intermittent cyclic mechanical tension (ICMT) could induce the calcification of endplate chondrocytes and long-term mechanical stimulation decreased the ank gene expression as was evident from our previous study 9 .…”
Section: Introductionmentioning
confidence: 61%
“…Mechanical cervical traction is an intervention that is often recommended for the treatment of patients with neck pain 8 . However, intermittent cyclic mechanical tension (ICMT) could induce the calcification of endplate chondrocytes and long-term mechanical stimulation decreased the ank gene expression as was evident from our previous study 9 .…”
Section: Introductionmentioning
confidence: 61%
“…6,34 In this study, we examined previously defined subgrouping criteria 34 and found that the validity of these criteria was underpowered and only suggestive of a subgroup-specific effect, based on the disability outcome after 6 months. The overall findings of this study indicate that patients who have cervical radiculopathy but do not meet the subgrouping criteria are still likely to optimize outcomes with mechanical traction in addition to an exercise program.…”
Section: Discussionmentioning
confidence: 89%
“…Motorized devices are typically used in clinical settings, but home units that use an over-door suspension system are also commonly provided to patients. Anecdotal reports suggest that home units may provide clinical benefit for patients with cervical radiculopathy, 6,12,38 but the effectiveness of these devices had not been previously evaluated in clinical trials. We found some benefit relative to an exercise-only approach, particularly among patients who seemed comfortable with the devices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations